Conservation agriculture: impacts on soil N2O emissions and adoption by farmers - Swan, Amy, author; Paustian, Keith, advisor; Ogle, Stephen, advisor; Sherman, Kathleen, committee member (Colorado State University. Libraries, 2012)
Agriculture is vulnerable to the effects of and a contributor to climate change, as a net source of anthropogenic greenhouse gases (GHG). However, agriculture has potential to reduce emissions and perhaps even become a net sink for GHG, through implementation of improved management practices. Previous research has shown that improved practices that reduce soil disturbance may sequester atmospheric carbon (C) in the form of soil organic matter. However, the impact of these practices on emissions of soil N2O, a potent GHG, are not as well understood. It is important to assess the effects of these practices on GHG emissions, as well as the potential of these practices to be used widely by farmers. I examined the effects of reduced soil disturbance from two conservation practices, no-till (NT) and conversion of cultivated cropland to perennial grassland, on N2O emissions, and evaluated adoption of NT by farmers in the Great Plains region of the U.S. I used a meta-analysis approach to evaluate changes in soil N2O emissions after a shift from full-inversion tillage (FT) to no-till (NT) on cropland and conversion of cultivated croplands to grasslands. Data were collected from published literature and analyzed with a linear mixed-effect modeling method, in which management practices, soil texture and climate were tested as fixed effect. After adoption of NT, soil N2O emissions were predicted to increase in humid climates by 0.4-0.8 kg N2O-N ha-1 yr-1, and decrease in dry climates, especially on soils with low clay contents, by as much as 1 kg N2O-N ha-1 yr-1. Changes in emissions after conversion of cropland to grassland were largely related to changes in N fertilizer rates. When lower rates of N were applied to grasslands, emissions were reduced by as much as 2 kg N2O-N ha-1 yr-1. When there was no change in N fertilizer, emissions were predicted to be higher than cropland rates, especially on moderate clay soils. Though the analysis predicted some clear changes in emissions after NT adoption and conversion of croplands to grasslands, further research is needed to better understand the interacting effects of management, climate and soil texture on soil N2O emissions. The practice of NT has been associated with many environmental benefits, including reduced soil erosion, lower run-off rates, increased soil organic matter, and improved soil structure. In addition to the potential of NT to sequester atmospheric C, results from my research show potential for NT to reduce N2O emissions in dry climates. Furthermore, the ability of NT to increase soil moisture retention may be a great benefit to crop production in dry climates, such as found in the Great Plains, U.S. However, NT is only used on about 17% of all croplands in this region. To evaluate the factors affecting NT adoption in the Great Plains, I conducted a regional analysis using county-level statistics and a local-level analysis using household surveys. Environmental variables, climate, slope, and soil texture, were predictors of adoption at the regional scale. High rates of adoption were predicted in dry, cool climates, which was consistent with the finding in the household surveys that NT farmers were more likely to cite soil moisture conservation as an important issue. Counties with more erodible soils (i.e. steep slopes (water) or high sand (wind)) had higher rates of NT adoption, possibly indicating that farmers in these counties were using NT to control soil erosion. Components of farm structure were also important, with ownership, cropping system, and Conservation Reserve Program (CRP) enrollment influencing NT adoption. Increased ownership rates and higher proportions of wheat cropping, led to lower rates in NT adoption. According to the household surveys, farmers with land enrolled in the CRP were more likely to use NT. Some operator characteristics and attitudes were found to be positively associated with NT adoption. Farmers who had been on their operation longer, expressed trust in the federal government, or hunted on their land for recreation were also more likely to adopt NT. Though some significant predictors of adoption in the Great Plains region may have an economic impact (climate, ownership and wheat cropping), no direct economic measures were found to be significant in predicting NT adoption in this analysis. Barriers to NT adoption in the region may be lack of education on the benefits of NT on crop production and the prevalence of continuous wheat cropping in parts of the region. Because NT adoption rates were higher among farmers who had participated in a government program (CRP) or expressed trust in the federal government, outreach may especially need to be targeted to farmers with less involvement in federal government programs. Though reason for the influence of ownership on NT adoption was unclear, future research may focus on the role of farm size in tillage decisions.
Keywords: conservation; surveys; no-till; nitrous oxide